2022
DOI: 10.1101/2022.11.30.518472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tethering by Uso1 is dispensable: The Uso1 monomeric globular head domain interacts with SNAREs to maintain viability

Abstract: Uso1/p115 and RAB1 tether ER-derived vesicles to the Golgi. Uso1/p115 contains a globular-head-domain (GHD), a coiled-coil (CC) mediating dimerization/tethering and a C-terminal region (CTR) interacting with golgins. Uso1/p115 is recruited to vesicles by RAB1. Paradoxically, genetic studies placed Uso1 acting upstream of, or in conjunction with RAB1 (Sapperstein et al., 1996). We selected two missense mutations in uso1 resulting in E6K and G540S substitutions in the GHD permitting growth of otherwise inviable … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…ULP1 is an interesting protein because it is unique to cyst-forming coccidia yet is structurally homologous to the conserved eukaryotic trafficking factor p115/Uso1. Studies in mammalian cells, Drosophila, and yeast have demonstrated that p115/Uso1 has a wide range of essential functions including tethering COPI vesicles to the Golgi, transporting vesicles from the ER to the Golgi, and facilitating SNARE complex assembly (48)(49)(50)(51)(52)(53). Loss of p115/Uso1 has been shown to result in fragmentation of the Golgi and accumulation of Golgi-derived vesicles (54).…”
Section: Discussionmentioning
confidence: 99%
“…ULP1 is an interesting protein because it is unique to cyst-forming coccidia yet is structurally homologous to the conserved eukaryotic trafficking factor p115/Uso1. Studies in mammalian cells, Drosophila, and yeast have demonstrated that p115/Uso1 has a wide range of essential functions including tethering COPI vesicles to the Golgi, transporting vesicles from the ER to the Golgi, and facilitating SNARE complex assembly (48)(49)(50)(51)(52)(53). Loss of p115/Uso1 has been shown to result in fragmentation of the Golgi and accumulation of Golgi-derived vesicles (54).…”
Section: Discussionmentioning
confidence: 99%